Quantum Hall effect in graphene with interface-induced spin-orbit coupling - Cysne, Tarik P.; Garcia, Jose H.; Rocha, Alexandre R. [UNESP]; Rappoport, Tatiana G. (American Physical Society (APS), 2018)
We consider an effective model for graphene with interface-induced spin-orbit coupling and calculate the quantum Hall effect in the low-energy limit. We perform a systematic analysis of the contribution of the different terms of the effective Hamiltonian to the quantum Hall effect (QHE). By analyzing the spin splitting of the quantum Hall states as a function of magnetic field and gate voltage, we obtain different scaling laws that can be used to characterize the spin-orbit coupling in experiments. Furthermore, we employ a real-space quantum transport approach to calculate the quantum Hall conductivity and investigate the robustness of the QHE to disorder introduced by hydrogen impurities. For that purpose, we combine first-principles calculations and a genetic algorithm strategy to obtain a graphene-only Hamiltonian that models the impurity.